Students’ Perception of Using Podcasts to Improve Listening Skills at the 3rd Semester Students of English Department at Universitas Bandar Lampung - Yanuar Dwi Prastyo; Ajeng Dianingsih; Siti Farhana (J-SHMIC : Journal of English for Academic, 2023)
The process of developing listening skills involves capturing the speaker's words, grasping their intended message, and encompassing the roles of both speaker and listener, along with the auditory aspect. This study aims to investigate how students perceive the use of podcasts for enhancing listening skills among 3rd semester students in the English Department of Universitas Bandar Lampung. Employing qualitative methods, the research was conducted with a participant group of 34 students from the university's English Department. Data collection encompassed surveys and interviews involving 5 students. The collected data was analyzed by merging insights from both the surveys and interviews. The findings demonstrate noticeable enhancements in students' listening skills through the integration of podcasts as a learning medium. Consequently, students' viewpoints regarding podcast utilization for improving listening skills exhibited advancements in effectiveness and distinctiveness. Students expressed appreciation for the captivating and informative nature of this learning medium.